Evaluation the Incidence of Genotoxic Effects of Artificial Food Favoring Additives in Bone Marrow Cells and Spleen Cells in Mice - Hassan, Ali F.; H. Jasem, Nibras (Iraqi Journal of Pharmaceutical Sciences, 2020)
Genetic material is the most important component of cells because it contains the genetic information; hence any disruption to the structure chromosome of cells could lead to very bad results. Genotoxicity use to evaluate the safety of any chemical compounds on genetic materials. Artificial food flavoring additive are chemical substances to produce specific placebo effects added to foods but impart specific flavor to it. The present study evaluates the genotoxic effect of artificial food flavoring additive on structure of chromosomes at three different concentrations (50%, 100%and 150%) on both bone marrow cells and spleen cells in mice for fourteen successive days. It was found that artificial food flavoring additive at concentration (50% and 100%) show not significant increase in total chromosomal aberration in both bone marrow cells and spleen cells when compare to negative control (p>0.05) meanwhile at concentration 150% it causes a significant increase when compare to negative control (p<0.05) .The results have been showed that artificial food flavoring additive had a genotoxic effect at (50%, 100% and 150%).